How non-invasive brain stimulation might invade our sphere of justice - Lavazza, A.; Garasic, M. D. (Journal of Cognitive Enhancement, 2017)
Non-invasive brain stimulation (NIBS) is proving to be an effective method to enhance cognitive skills and motor coordination, which makes it a precious tool both in the intellectual sphere and in sports. Accordingly, in selective-competitive contexts, the use of NIBS can threaten the fairness and produce unexpected social composition effects. To avoid those negative consequences, it might be recommended that people should declare the use of enhancers of any kind, including those that are not explicitly prohibited. But the duty of disclosure seems particularly problematic to be enforced with NIBS, as it is not currently detectable. Moreover, considering the fact that NIBS has very different enhancement effects on each individual, all these elements may create strong performance inequalities and consequent discrimination, if NIBS were to become widespread. In this paper, within a Rawlsian theoretical framework, we highlight the risks posed by this new performance-enhancing technology and we propose compelling moral reasons for some forms of regulation of non-clinical use of NIBS.